In vitro assessment of pesticides capacity to act as agonists/antagonists of the thyroid hormone nuclear receptors - Yanis Zekri; Laure Dall Agnol; Frédéric Flamant; Romain Guyot (iScience, 2021)
Summary: Chemicals acting as thyroid hormone disruptors (THDs) are of a particular concern for public health, considering the importance of this hormone in neurodevelopment and metabolic processes. They might either alter the circulating level of thyroid hormone (TH) or interfere with the cellular response to the hormonal stimulation. In order to assess this later possibility we selected 39 pesticides and combined several in vitro tests. Reporter assays respectively addressed the transactivation capacity of the full-length TH nuclear receptor TRα1, the transactivation capacity of its C-terminal ligand binding domain, or the ability of the hormone to destabilize the interaction between TRα1 and the transcriptional corepressor NcoR. Although some pesticides elicit a cellular response, which sometimes interferes with TH signaling, RNA-seq analysis provided no evidence that they can act as TRα1 agonists or antagonists. Their neurodevelopmental toxicity in mammals cannot be explained by an alteration of the response to TH.